200 Boredom Busters! : The Bumper Book of Brilliant Ideas - Scott, Paul (London Dorling Kindersley, 1999)
Contains 200 fun to make projects and suggestions for activities such as playing bicycle polo, building a tepee, constructing a kite, creating a martian landscape, shooting a video, inventing a code, learning magic tricks, and baking party treats. Suggested level: primary, intermediate.
Include Color Illustrations
Keywords: Amusements -- Handicraft -- Creative thinking